IMPLEMENTASI PROGRAM BANTUAN BAGI PELAKU USAHA MIKRO (BPUM) DI MASA PANDEMI COVID-19 OLEH DINAS KOPERASI KOTA PEKANBARU - Putri Cintia Pasza; Febri Yuliani (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
In the midst of the rapid development of UMKM, their movement has decrreased dwe to the emergence of Covid-19, which has a direct impacts on economics turnover, especially for UMKM. The government through the Ministry of Cooperatives and UKM distributes Presidential Assistance for Micro Business Actors (BPUM). The application for BPUM is carried out one door, namely through the office in charge of cooperatives and UKM in the district/city. BPUM or Assistance for Micro Business Actors is one type of BLT (Direct Cash Assistance) provided by the government. Targeting micro, small and medium entrepreneurs, this assistance is channeled directly into the accounts of BPUM recipients and is aimed at those who meet the requirements and are registered as recipients. The purpose of this study was to determined the Implementation of the Assistanced Program for Miccro Business Actors (BPUM) durings the Covid-19 Pandemics by the Pekanbaru City Cooperative Offices. The types of researched used is qualitatives research and data collections techniques based on interviews, observations, and documentations. The results of this study are that the implementation of the BPUM program at the Pekanbaru City Cooperative Service is quite good, such as forming a special team in implementing the BPUM program so that it can run well but there are still some obstaclesd that occur during implementation, thus hampering the process of implementing the BPUM program.